Changes in Fiber Components in Fermented Moringa Leaf Flour using Trichoderma koningiopsis AA1 - Riyadi, Dhimas Ivan; Wahyu Mulyono, Ali Mursyid; Husein, Muhammad; Sukaryani, Sri; Qui, Nguyen Hoang (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2025)
This study aimed to investigate the effect of fermenting Moringa leaf flour using Trichoderma koningiopsis AA1 (STk-AA1) with different fermentation durations (0, 4, and 8 days) on the content of crude fiber, Neutral Detergent Fiber (NDF), Acid Detergent Fiber (ADF), cellulose, and hemicellulose. A Completely Randomized Design (CRD) was used, consisting of three treatments with three replications each. The data were analyzed using Analysis of Variance (ANOVA) with a significance level of P<0.05. The results showed that fermentation of Moringa leaf flour with STk-AA1 had a significant effect on increasing the levels of crude fiber, NDF, ADF, cellulose, and hemicellulose. The increase in crude fiber, NDF, and ADF was attributed to the presence of chitin in the fungal cell wall, while the increase in cellulose and hemicellulose content was due to the enzymatic activity produced by STk-AA1, such as cellulase and hemicellulase, during the fermentation process. Based on these findings, further research is recommended to explore different strains of STk-AA1 and the effects of temperature and humidity during fermentation to optimize fiber content and other components.